Hematochemical hallmarks as markers of pulmonary TB severity: A multicenter cross-sectional study - Francesco Di Gennaro; Giacomo Guido; Sergio Cotugno; Francesco Cavallin; Mariantonietta Pisaturo; Lorenzo Onorato; Federica Zimmerhofer; Luca Pipitò; Giuseppina De Iaco; Giuseppe Bruno; Massimo Fasano; Agostina Pontarelli; et al. (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Background: Identifying accessible and reliable biomarkers for tuberculosis (TB) severity is crucial for improving patient management. This study evaluates hematological findings as potential indicators of TB severity in a large multicenter Italian cohort. Methods: This retrospective, multicenter, cross-sectional study analyzed hematological parameters (hemoglobin, white blood cells, inflammatory indices, hepatorenal function, albuminuria) in 577 TB patients from 10 Italian centers (2018–2023). Severe TB was defined by at least two criteria: TIMIKA score > 60, sputum conversion time > 21 days, or need for oxygen supplementation. Statistical analyses included receiver operating characteristic curve (AUC) evaluation, calibration curves, and clinical utility. Results: Of the patients, 30.3 % were classified as severe, 60.2 % as non-severe, and 9.5 % as uncertain. AUC values for predicting severe TB ranged from 0.51 to 0.56 across hematological variables. Anemia and elevated CRP demonstrated sensitivities of 0.71 and 0.74, respectively. Models using continuous or categorical hematological variables achieved AUCs of 0.61 and 0.65, showing poor calibration and limited clinical utility in the 30–60 % threshold range. Conclusions: Hematological markers, while rapid and cost-effective, demonstrated limited discriminative ability for TB severity. Further studies are required to develop reliable predictive models, integrating additional clinical and molecular data.